Does financial technology matter? Evidence from the Indonesia healthcare industry during the COVID-19 pandemic - Liliana Inggrit Wijaya; Zunairoh Zunairoh; Andri Rianawati; Vincentius Riandaru Prasetyo; Indro Harianto (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
The Covid-19 pandemic has created various new restrictions, including restrictions on direct interaction in the administrative process of hospitals. In fact, the administrative process in Indonesian hospitals is still complex, not well organized, and has not used technology properly. This study aims to analyze the effect of financial technology (fintech) and financial literacy on the efficiency of the Indonesian healthcare industry during the Covid-19 pandemic era. This study uses a quantitative method with an online survey for data collecting. The purposive sampling was applied to get 225 respondents. The dependent variable is financial technology usage, which is measured through three perceptions of fintech users: perceived ease of use, perceived usefulness, and internet usage of all healthcare service users in the healthcare industry in Indonesia. The moderating variable adopted in this study is financial literacy, which is a combination of the understanding (knowledge), skills, attitude, and ability to make sound judgement and decision (behavior) on personal financial matters resulting in individual financial well-being. This study uses the SEM (Structural Equation Modeling) method to analyze the efficiency of the healthcare industry. The study results show that perceived ease of use and perceived usefulness have an effect on fintech; fintech has a positive effect on efficiency, where financial literacy also strengthens the effect of fintech on efficiency in the Indonesia healthcare industry during the Covid-19 pandemic. The results of this study are expected to make a significant contribution to the development of the healthcare industry that currently becomes a top priority, given the urgency in handling public health, including Covid-19 patients. Additionally, this research provides a theoretical contribution by increasing fintech literacy in the healthcare industry in increasing efficiency during the Covid-19 pandemic. While practical contribution is about giving new insight to consider the technology in improving management process in healthcare industry.
Keywords: F64; F65; G; G01; G38; 330; Covid-19; Financial technology; Efficiency; Financial literacy; Healthcare industry